"New World, new rules: the changing role of the American Corporation" - "Whiteman, Marina" (Boston, 1999)
"New World, New Rules" is a compelling chronicle of the American corporation's changing role, as well as a perceptive look at what these changes mean for both business and society.Throughout much of the twentieth century, the American corporation was looked to as a bedrock of stability and security, a benevolent institution whose power and influence was a trusted force in business and society alike. For better or worse, this corporation no longer exists. Intense competition, globalization, and economic flux have all profoundly altered corporate America's relationship with employees, shareholders, communities, government and society. Author Marina Whitman shares both the personal experiences and in-depth research from her distinguished career as a business leader, academic, government advisor, and influential corporate strategist. One of the first women appointed to a major corporate board, a former vice president at General Motors, and a former member of the President's Council of Economic Advisers, Whitman is currently a director of five major multinational corporations and a renowned scholar of economics and public policy. Here is the remarkable account of what she has observed during a period of unprecedented business upheaval.
Keywords: Corporations-United States